TYPOLOGY OF FAMILIES IN NEED OF SOCIO-PSYCHOLOGICAL ASSISTANCE (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article devoted to the definition of a typology of families in need of social and psychological assistance. To determine the families who need social support, long used different concepts that characterize the negative features of life of families with children, dysfunctional families, family social risk, dysfunctional family, problematic family. Due to the variety of definitions of families in need of social assistance in the scientific literature, and in legal documents, there is a lot of confusion, including the substitution of concepts and there is a conflict between them. Analysis of practice of social workers showed that the lack of science-based typology of families in need of social and psychological assistance is a serious obstacle in working with them. Due to huge list of features of "the family of the difficult life circumstances" social workers have to put on the record so many families that exceeds the capacity of the workload of the relevant services. This is due to lack of clarity and substitution of concepts presented in the regulatory framework, many signs do not correspond to the nature of the term "the family of the difficult life circumstances" one and the same sign has a double meaning. It is shown that the lack of adequate typology of families and determine the type of assistance they require leads to resources that provide those families who are not interested in solving their problems.Empirically proved that the features of the concept of "the family of the difficult life circumstances" does not correspond to the real causes of family problems. Dysfunctions within family relationships is always a determination of deviations in behavior. Identify dysfunctional, but apparently happy family can be identified because of the patient. The proposed typology of families in need of social and psychological assistance is built according to the psychological determinants.
Keywords: Family, social and psychological assistance determinants.